Why Does the Recently Adopted Performance Measurement System in Indonesian Local Government Not Work? - Heru Fahlevi; Dharni Nuzulla; Hasan Basri (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2018)
The purpose of this study is to gain insight on the implementation of a newly adopted Performance Measurement System (PMS) in Sabang local government – Indonesia. It is a case study based qualitative research which was carried out at the local government of Sabang. Data were collected through document analysis, questionnaires, and followed by semi-structure interviews. The questionnaires were distributed to key officers of 7 working unit/departments (or Satuan Kerja Perangkat Daerah) out of 31 departments in total within the city of Sabang. The interviewees are head of the departments, the secretary, head of program and reporting division of each working unit. The data were analyzed by using qualitative data analysis technique. The institutional theory was used as a basis for analyzing and discussing the results obtained. This study uncovers that the PMS concept and functions have not fully understood by most of the key officers. Consequently, the recently developed PMS is not utilized optimally and thus it does not contribute to a better performance management system of the local government. The reasons why it is now work well are incapacity of the human resource, unclear job description, lack of organizational commitment and the absence of the performance evaluation. Thus, it can be concluded that pre-requirements and pre-condition need to be fulfilled before adopting a new PMS, especially where the PMS is not initiated by the organization itself, rather imposed by the central government or other organization.Tujuan dari penelitian ini adalah untuk mendapatkan pemahaman yang mendalam mengenai implementasi Sistem Pengukuran Kinerja (SPK) yang baru diadopsi di pemerintah daerah Kota Sabang - Indonesia. Penelitian ini adalah penelitian kualitatif yang menggunakan desain studi kasus padai pemerintah daerah Kota Sabang. Data dikumpulkan melalui analisis dokumen, kuesioner, dan diikuti oleh wawancara semi-struktur. Kuesioner dibagikan kepada staf senior dari 7 unit / departemen kerja (Organisasi Perangkat Daerah/OPD) dari total 31 OPD di kota Sabang. Narasumber yang diwawancarai adalah kepala OPD, sekretaris, kepala program dan divisi pelaporan dari masing-masing unit kerja. Data dianalisis dengan menggunakan teknik analisis data kualitatif. Teori institusional digunakan sebagai dasar untuk menganalisis dan mendiskusikan hasil yang diperoleh. Studi ini menemukan bahwa konsep dan fungsi SPK belum sepenuhnya dipahami oleh sebagian besar narasumber. Akibatnya, SPK yang baru dikembangkan tidak dimanfaatkan secara optimal dan sehingga tidak berkontribusi pada sistem manajemen kinerja yang lebih baik di pemerintah daerah yang diteliti. Sejumlah penyebab yang ditemukan adalah kurangnya kapasitas sumber daya manusia, deskripsi pekerjaan yang tidak jelas, kurangnya komitmen organisasi dan kurang optimalnya sistem evaluasi kinerja. Dengan demikian, dapat disimpulkan bahwa sejumlah prasyarat dan kondisi harus dipenuhi sebelum mengadopsi sebuah SPK baru, terutama di mana SPK tidak dikembangkan sendiri, melainkan diperintahkan oleh pemerintah pusat atau organisasi lainnya